Spatial Structures : Introducing the Study of Spatial Systems in Human Geography - Johnston, Ronald John, author 268506 (London, United Kingdom : Methuen, 1973)
This book synthesizes the mass of material into an introduction to the study of spatial systems. Geographic literature of the time stressed the influence of the distance between places on both location decision-making and movement patterns, arguing that the spatial system is an ordered set of interacting locations. This system is created by human decisions, influenced by the distance factor, and the system’s morphology constrains further activities, including those which would alter it. Spatial Structures outlines the development of such systems, their present organization, and the ways in which they are changing. These themes are dealt with in three main chapters which focus on different spatial scales – the individual city, the nation state and the international system, within a simple classification of spatially organized activities.